Identifying monetary policy in a small open economy under fixed exchange rates - Niels C. Beier; Peter E. Storgaard (Danmarks Nationalbank, 2006)
We demonstrate how to identify monetary policy under fixed exchange rates in a structural vector autoregression (SVAR) using Denmark as a case study. The identifying restrictions are compared to SVARs for flexible exchange-rate regimes. Our basic model generates a plausible central-bank reaction function, and the responses to monetary shocks are in accordance with theory. We extend the basic model and econometric approach to incorporate the central bank's interventions on the foreign-exchange market.
Keywords: F31; E52; C32; 330; foreign exchange intervention; monetary policy; structural VAR; exchange rate; reaction function; fixed exchange rate